A MORPHOLOGICAL EXPERIMENTON ANTECEDENTS OF SOCIAL MEDIA USAGE: STRUCTURAL EQUATION MODELLING APPROACH - C. Revathy; P. Balaji (International Journal of Psychosocial Rehabilitation, 2020)
The present study was aimed to conduct morphological experiment on social media usage behaviour of college students through structural equations modelling approach. The samples of 275 were collected from college students of Chennai city to understand the factors significantly predicting the social media usage. The path coefficients for all the four hypotheses were supported in the present study. The smart phone and internet usage variables such as, creativity factor, experience factor, demonstration factor and convenience factor have significant and positive influence on the social media usage factors andlife style change is the cause for higher penetration of smart phone and internet usage and social media usage in technological environment.